Development And Characterization Of Nano Oil Palm Ash As Filler In Phenolic Resin For Bonding Oil Palm Veneer And Hybrid Plywoods - Alam, Che Ku Abdullah Che Ku (2020)
The focus and interest in the utilization of oil palm ash (OPA) is high, mainly due to their renewable material, opportunity to enhance the properties and possibility to use in a wide range of applications. This thesis discusses the optimization of OPA nanoparticles preparation and to study the performance of OPA nanoparticles in the plywood composite. A statistical analysis based on the Taguchi method has been used to find the optimal parameters for the preparation of OPA nanoparticles by using ball milling technique. L9 orthogonal array and signal-to-noise (S/N) ratio are applied to study performance characteristics of the selected parameters which are milling time (hours), milling speed (rpm), and size of stainless-steel balls. The size distribution of the OPA nanoparticles was examined by the particle size analyzer and TEM analysis. In this study, a statistical analysis and confirmation test showed that the ball`s size (20 mm) was the most influential parameter to produce OPA nanoparticles followed by milling time (24 hours) and milling speed (90 rpm). In order to explore the potential of the OPA nanoparticles in resin application, the phenol formaldehyde (PF) resin filled different loading of OPA nanoparticles were prepared. The qualitative characterizations of PF resin nanocomposite filled OPA nanoparticles were investigated by FT-IR, TGA, XRD and FESEM. It was indicated that OPA nanoparticles remarkably improved the thermal stability and crystallinity of PF resin nanocomposites.